Charming candle bushes adding splendor to low hill areas - Thakur, Priyanka; Gupta, Y C; Joshi, A K (Indian Horticulture, 2019)
The candle bush is an important medicinal plant, as well as an attractive flowering plant in tropical areas. Botanically, known as Cassia alata, it belongs to family Caesalpiniaceae and commonly known as Candlebra bush, Christmas candle, popcorn senna, golden candlestick, empress candle plant, ringworm tree. It is an attractive shrub named 'Yellow candle bushes' for its flower buds which grow in one column and look like fat waxy yellow candles. Its leaves fold together at night.